1991
DOI: 10.1116/1.585795
|View full text |Cite
|
Sign up to set email alerts
|

Radio frequency or microwave plasma reactors? Factors determining the optimum frequency of operation

Abstract: It is now generally accepted that the frequency ω/2π at which a high frequency (hf) discharge is sustained has considerable influence on the properties of the plasma. For example, the electron density obtained for a given hf power density deposited into the plasma is usually higher at microwave than at radio frequencies (rfs). This paper reviews a series of experiments at the Université de Montréal designed to investigate the influence of ω on the power balance between the hf field and the plasma, and the plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(57 citation statements)
references
References 0 publications
2
51
1
Order By: Relevance
“…The low protein adsorption in this study compared with those reported in the current study could be attributed to a higher C-O component (84%), lower protein concentrations and differences in plasma-processing parameters such as the pulsed plasma conditions and the use of a tetraglyme monomer [30]. Previous studies have shown that tri-and tetraglyme plasma polymer films are extremely effective in reducing surface protein adsorption [15,20]. , for which the oxygen content is higher (33% O, 67% C).…”
Section: Characterization Of the Films Using Atomic Force Microscopycontrasting
confidence: 54%
See 2 more Smart Citations
“…The low protein adsorption in this study compared with those reported in the current study could be attributed to a higher C-O component (84%), lower protein concentrations and differences in plasma-processing parameters such as the pulsed plasma conditions and the use of a tetraglyme monomer [30]. Previous studies have shown that tri-and tetraglyme plasma polymer films are extremely effective in reducing surface protein adsorption [15,20]. , for which the oxygen content is higher (33% O, 67% C).…”
Section: Characterization Of the Films Using Atomic Force Microscopycontrasting
confidence: 54%
“…The 20 and 50 W films were also measured against aqueous solution using NR, with the neutron beam reflecting from the film/water surface. Three different solvents ('contrasts') were used for the 20 Changing the deuteration level of the solution changes the refractive index of the water and therefore the scattering contrast of the system. An analysis identical to that carried out on the dry films was performed.…”
Section: Reflectometry Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this different behavior, which is reflected in surface properties (see below), is still an area of current research. Perhaps the molecules are subjected to the higher electromagnetic field and the static DC field across the hot electrode in RF discharges and are consequently destroyed more readily than by microwave excitation [41,42] Figure 14. Detail of the IR spectrum of PECVD parylene N and CVD parylene N.…”
Section: Spectral Identificationmentioning
confidence: 99%
“…[24,25,26]. In this section we first briefly review the theory behind VHF PECVD, its advantages and then present the specific results from literature obtained in nc-Si material.…”
Section: History Of µC-si:hmentioning
confidence: 99%